Epidemiology of malaria and hematological analysis in district Dir (lower), Pakistan - Wali Khan; Hussain, Tahir; Yar, Asfand; Ullah, Sayed attiq; Dr Hameed Ullah; Syed Sohail Ahmad (International Journal of Pathology, 2024)
Background: Malaria is considered as a tropical disease, in developing countries. Among all parasitic infections malaria is most widespread and devastating disease. According to WHO malaria is endemic in 24 countries. Methods: This cross-sectional study was conducted at Department of Medical Laboratory Technology University of Haripur. Total 995 samples were collected at District Head Quarter Hospital (DHQ), Tehsils Hospitals (THQs), and other private laboratories in District Dir (Lower). These samples were processed to observe the shape of RBCs as well as plasmodium species in the smear microscopically, and for hemoglobin estimation. Data was analyzed through SPSS version-21. Results: Highest percentage of malaria was recorded in Munda (35.17%) followed by Timergara (19.59%) whereas the lowest number of cases were found in Khall (5.02%). Prevalence of P. vivax was (98.0 %) and P. falciparum was (2 %) in district Dir Lower. Mean red blood cell count (RBCs) was 4.2±0.64 mm3 while mean Hb was 11.0±1.99g/dl. Based on different age categories, the highest RBCs and Hb levels were found in age group 41-50 years, whereas the lowest RBCs were found in age group 11-20 years while the lowest Hb levels were recorded in group 1-10 years. In associated diseases, the upper respiratory tract infections (URTIs) were the most frequent (20%) followed by diarrhea (18%). Mean Hb of males was 11.8±1.53 g/dl while the mean Hb of female was 11.5±5.384 g/dl. Hb in both males and females were low as compared to the standard. However, as compared to females, Hb of males were significantly lower with p-value <0.001. Conclusion: We concluded that males are more commonly infected from malaria as compared to females. Males and children were found to have low Hb as compared to females and higher age group patients. URTIs and diarrhea were the most common associated illness.